Empowering Orphaned Children Through Counseling: Enhancing Life's Meaning - Khairunnisa, Khairunnisa; Nurhayani, Nurhayani (citeus, 2025)
Counseling services are very important to help children find meaning in life and overcome the various problems they face as adults. Children are the future of the nation and need attention; many of them lose their identity during adolescence but can lead good lives with an intact family. The aim of this study is to understand the implementation of counseling services in developing the meaningfulness of life for orphans at the Al-Washliyah Orphanage in Lubuk Pakam, Indonesia. The method used is a qualitative approach. The subjects of this study are the children of the Al-Washliyah Orphanage in Lubuk Pakam, Lubuk Pakam District, Deli Serdang Regency, North Sumatra, Indonesia. The results of the study show that the success of the counseling services at the Al-Washliyah Orphanage in Lubuk Pakam can be seen from several indicators, such as understanding a clear purpose in life, knowing how to find meaning in daily activities, recognizing their potential and knowing how to develop it, valuing life experiences, having positive relationships with others, creating a harmonious family within the orphanage, feeling gratitude and accepting themselves without comparing themselves to others, being optimistic about their life choices, learning valuable lessons from suffering, and having spirituality with the belief that Allah SWT loves them. The activities provided by the counselors to the children in the orphanage include religious activities such as prayer guidance, teaching reading and writing of the Qur'an, and moral guidance. The children at the orphanage can understand their purpose in life through various processes and activities conducted during their stay.